Total saponins of Panax notoginseng protected rabbit iliac artery against balloon endothelial denudation injury - CHEN Si-wei; LI Xiao-hong; YE Kai-he; JIANG Zuo-feng; REN Xian-da (Acta Pharmacologica Sinica; Vol 25, No 9 (September 2004): Acta Pharmacologica Sinica, 2016)
AIM: To investigate whether total Panax notoginseng saponins (PNS) could protect endothelium of rabbit iliac artery against balloon endothelial denudation (BED) injury. METHODS: The morphology changes of the endothelium were observed with scanning electron microscope (SEM) and hematoxylin and eosin stain after BED of rabbit iliac artery at 0, 4, 6, and 8 week respectively. Vascular endothelial growth factor (VEGF) and matrix metalloproteinase-2 (MMP-2) was also determined by immunohistochemistry. PNS 10, 30, and 50 mg/kg were administered iv per day from 2 d before to 4 weeks after operation. RESULTS: The endothelium was denudated completely after BED. At the 4th week the endothelium was repaired in some degree, then recovered gradually at 6 and 8 week. The degree of intimal thickening at 4 week was significantly greater than that at 0, 6, or 8 week. The sequence of VEGF or MMP-2 staining from strong to weak was 4, 6, 0, 8 week, and normal control. However at 4 week, endothelial regeneration in PNS 30 and 50 mg/kg groups was significantly faster than that in saline group. The intimal thickness was significantly decreased and expressions of VEGF and MMP-2 were both down-regulated in PNS 30 or 50 mg/kg groups compared with saline control group. CONCLUSION: PNS promoted the endothelial regeneration and reduced ECM thickening, which was related to regulation of the expression of VEGF and MMP-2. PNS may have sustained antirestenotic effect after BED.